In Vivo Anatomical Variations in the Lateral Femoral Cutaneous Nerve in Children - Lise Langeland Larsen; Line Kjeldgaard Pedersen; Ole Rahbek; Bjarne Møller-Madsen (Children)
Background: The anatomic pathways of the lateral femoral cutaneous nerve (LFCN) have primarily been reported in adult in vitro populations with limited branching patterns. Children with hip disorders may require surgical treatment with an anterior approach, and the LFCN is a structure at risk. The aim of our study was to photographically verify the initial six-centimeter pathway of the LFCN in children measured from its appearance at the anterior superior iliac spine (ASIS). Method: A total of 31 children underwent pelvic osteotomy, including three bilateral. The nerve was identified and isolated in the subcutaneous layer. Standardized photographs were obtained. Our outcome parameters were type of pelvic exit, branching pattern, distance from the pelvic exit to the ASIS, and nerve thickness and appearance, categorized as straight or curved. Results: 91.3% of nerves passed medially to the ASIS. A total of 74% of the nerves showed a splitting branching pattern, and 9% had a branching pattern of more than four. The mean distance from pelvic exit to the ASIS was 17 mm, and the mean nerve thickness was 2.7 mm. Conclusions: In contrast to adult anatomy, our study shows that the LFCN has two or more branches in 74% of patients. Thus, based on our observations, surgeons should carefully dissect the subcutaneous tissue around the LCFN due to the numerous anatomical variations to avoid iatrogenic damage to the nerve.